1988
DOI: 10.1103/physrevb.37.2320
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of antiferromagnetism and superconductivity in a mean-field theory of high-T_{c} superconductors

Abstract: %'e investigate a mean-6eld theory of the Hubbard model in the large on-site correlation limit, allowing for the possibility of a commensurate spin4ensity wave together with sand d-wave-like superconductivity.As a function of t/U and band filling, the resulting phase diagram exhibits' phases which are simultaneously superconducting and antiferromagnetic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
67
1

Year Published

1989
1989
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(69 citation statements)
references
References 15 publications
1
67
1
Order By: Relevance
“…The spectral weight of this mode will be much smaller than the slightly higher energy bulk contribution from outside the vortex cores, and will consist of a feature of width dk ᐉ 21 (resolution of the Bragg reflections may not be feasible). For slightly larger H, the distinction between the localized and delocalized contributions will disappear, and we expect that a full dynamic spin structure with Bragg reflections may be resolved in neutron scattering experiments, with the lowest energy mode obeying (8). It is also interesting to note that, even for small H, repulsion between the SC and SDW order parameters described by the y term in (1) will lead to an interesting structure in the spatial form of jc͑x͒j on the scale ᐉ which may be significantly larger than the bare SC coherence length (unity in our units).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The spectral weight of this mode will be much smaller than the slightly higher energy bulk contribution from outside the vortex cores, and will consist of a feature of width dk ᐉ 21 (resolution of the Bragg reflections may not be feasible). For slightly larger H, the distinction between the localized and delocalized contributions will disappear, and we expect that a full dynamic spin structure with Bragg reflections may be resolved in neutron scattering experiments, with the lowest energy mode obeying (8). It is also interesting to note that, even for small H, repulsion between the SC and SDW order parameters described by the y term in (1) will lead to an interesting structure in the spatial form of jc͑x͒j on the scale ᐉ which may be significantly larger than the bare SC coherence length (unity in our units).…”
mentioning
confidence: 99%
“…We argue here that the experiments can be understood by assuming that the superconductor (SC) is in the vicinity of a bulk quantum phase transition to a state with microscopic coexistence of SC and spin density wave (SDW) orders; the latter state has been considered in a number of studies [8][9][10][11][12][13][14], and has been observed in excess-oxygendoped La 2 CuO 41y [15]. The magnetic field, H, drives the SC phase closer to the SC 1 SDW phase -see Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The slave particle mean-field methods 3,4,5,6,7,8,9 were the first approaches to overcome this problem. In these methods, the constrained electron operators are expressed in terms of auxiliary fermions and bosons.…”
Section: Introductionmentioning
confidence: 99%
“…A large volume of work exists that focuses on the various details of the coexistence phenomenon. Some of the theoretical attempts include mean field studies of t-J and Hubbardlike models which confirm the coexistence of magnetic and superconducting order 4,5 . The coexistence is suggestive of the presence of short range AF correlations in SC state that are probed by inelastic neutron scattering experiments via an enhanced scattering intensity near the AF wavevector (π, π) 6,7,8,9 .…”
Section: Introductionmentioning
confidence: 99%